2016
DOI: 10.1021/acs.analchem.6b02720
|View full text |Cite
|
Sign up to set email alerts
|

A Reversible Nanolamp for Instantaneous Monitoring of Cyanide Based on an Elsner-Like Reaction

Abstract: It is well-known that cyanide ion (CN) is a hypertoxic anion, which can cause adverse effects in both the environment and living beings; thus, it is highly desirable to develop strategies for detecting CN, especially in water and food. However, due to the short half-life of free cyanide, long analysis time and/or interference from other competitive ions are general challenges for accurate monitoring of CN. In this work, through the investigation on the sequence-dependent optical interaction of DNA-CuNPs with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…To reveal the truth, herein, we exploited a mitochondria-anchored molecular rotor, ethyl-4-[3,6-bis­(1-methyl-4-vinylpyridium iodine)-9 H -carbazol-9-yl)] butanoate (BMVC), as a molecular viscosimeter for real-time observation of mitochondria viscosity variation during mitophagy process in live cells. BMVC is a novel class of carbazole derivative possessing the distinct ability to bind DNA secondary structure and human serum albumin (HSA), and hence is the object of our investigations in G-quadruplex-based sensing, two-photon indicator for DNA conformation changes, and HSA-modulated fluorescence amplification. In this work, we found that BMVC is a mitochondria-anchored viscosity-sensitive molecular rotor that allows for investigating changes in mitochondrial viscosity. The rotor units display a desirable off–on fluorescence sensitive toward the mitochondrial viscosity because of the free rotation restricted around the vinyl bond connecting the carbazol core and the pyridium group.…”
mentioning
confidence: 99%
“…To reveal the truth, herein, we exploited a mitochondria-anchored molecular rotor, ethyl-4-[3,6-bis­(1-methyl-4-vinylpyridium iodine)-9 H -carbazol-9-yl)] butanoate (BMVC), as a molecular viscosimeter for real-time observation of mitochondria viscosity variation during mitophagy process in live cells. BMVC is a novel class of carbazole derivative possessing the distinct ability to bind DNA secondary structure and human serum albumin (HSA), and hence is the object of our investigations in G-quadruplex-based sensing, two-photon indicator for DNA conformation changes, and HSA-modulated fluorescence amplification. In this work, we found that BMVC is a mitochondria-anchored viscosity-sensitive molecular rotor that allows for investigating changes in mitochondrial viscosity. The rotor units display a desirable off–on fluorescence sensitive toward the mitochondrial viscosity because of the free rotation restricted around the vinyl bond connecting the carbazol core and the pyridium group.…”
mentioning
confidence: 99%
“…Due to the extensive research and application of DNA-templated fluorescent NCs, their fluorescence properties have been extensively studied in recent years [1,5,8]. The DNA template shows significant effects on the fluorescence characteristics of NCs.…”
Section: Synthesis Of Dna-templated Fluorescent Nanoclustersmentioning
confidence: 99%
“…Fluorescent NCs are the well-defined sub-nanometer size structures that are formed by a few to a hundred metal atoms with high emission. Current fluorescent materials that are used in sensing applications mostly include organic fluorescent dyes, up-conversion nanomaterials, quantum dots, fluorescent proteins, et al The easy photobleaching and small Stokes shifts of organic fluorescent dyes restrict their applications in complex samples [8,9]. Most of quantum dots and up-conversion nanomaterials are physically large-size and potentially toxic, which limit their practical applications in biochemical analysis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, cyanide fluorescent probes have been developed on the basis of the specific nucleophilic reactivity of cyanide to electrophilic double bonds, such as CC, CO, CN, CS, or CN + . Nevertheless, most of the reported fluorescent probes for determining cyanide in water samples and food samples only displayed fluorescence turn-on response. A major limitation of the fluorescence turn-on probe is that the signal output is vulnerable to factors such as excitation intensity, probe concentration, and instrumental efficiency. By contrast, a ratiometric fluorescent probe can effectively eliminate the above-mentioned limitations and consequently provide more accurate analysis. , In addition, the preparation of the reported probes generally needs sophisticated synthesis procedures.…”
Section: Introductionmentioning
confidence: 99%